The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1517-83822014000400034
|View full text |Cite
|
Sign up to set email alerts
|

Community-associated methicillin-resistant Staphylococcus aureus in non-outbreak skin infections

Abstract: The aim of this study was to determine the prevalence of Staphylococcus aureus and risk factors for the acquisition of MRSA (Methicillin Resistant Staphylococcus aureus) as the main cause of skin and soft tissue infections. S. aureus were characterized for the presence of PVL, TSST-1 and mecA genes. SCCmec typing was carried out in mecA positive strains and PFGE was performed only in these strains. During the study period, 127 outpatients attending a dermatology clinical the Botucatu Medical School, a regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
2
15
1
Order By: Relevance
“…The TSST-1 gene was identified in 5% of the S. aureus isolates, all MSSA. Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…The TSST-1 gene was identified in 5% of the S. aureus isolates, all MSSA. Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…It was previously reported that S. aureus was responsible for 8-18% of all skin diseases in travelers returning from abroad without specific geographical repartition [16]. No mecA resistance genes were found in our survey which does not corroborate results obtained in patients living in or returning from developing countries and suffering skin infections [16][17][18][19]. This could result from the small effective of S. aureus skin infections in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of MRSA was higher in our study compared to similar studies from Turkey (31.81%) (16), Beijing (3%) (17), Egypt (47.37%) (18), and Sao Paulo (10.6%) (15). It was similar to the rate reported from Torrance, California (66.57%) (3), and lower than the rate found in a general report from the United States (79%) (19).…”
Section: Discussionsupporting
confidence: 68%
“…Identification of the mecA gene is the most reliable method to identify MRSA carriers early in their hospitalization. This allows the prompt initiation of isolation measures to minimize MRSA transmission to other patients and health care providers (15).…”
Section: Discussionmentioning
confidence: 99%